0257 Preliminary Findings: Attentional Bias for Food Cues Unrelated to Time Awake or Circadian Phase During Forced Desynchrony in Adolescents. (27th May 2020) - Wong, P M; Barker, D H; Raynor, H A; Hart, C; Carskadon, M A
Abstract: Introduction: Sleep quantity and quality influence attentional bias, and attentional bias for food cues has been associated with body weight. Whether the endogenous circadian cycle and/or time from awakening to bedtime contribute to attentional bias for food and differences in weight remain unclear. Using a 28-h forced desynchrony (FD) design, we hypothesized that adolescents with overweight (OW) and obesity (O) would have more attentional bias for food cues later in the wake episode and at a later circadian phase compared to adolescents with a healthy weight (HW). Methods: 50 (28 male) adolescents (12-15yr) completed 7 FD cycles. Participants completed an attentional bias task that included three food word categories (savory, sweet, fruits/vegetables) and one non-food word category (school supplies). The task was completed at 6 fixed times each cycle: Task 1 was 1.3h after scheduled awaking, Task 2 was 2h after Task 1, and Tasks 3–6 followed at 3-h intervals. Weight categorization used body mass index (BMI) percentiles (CDC): HW (>5 th and <85th; n=24), OW (85 th and <95th; n=13), or O (≥95th; n=14). Endogenous circadian period was determined using salivary melatonin onsets (Mean: HW=23.88h; OW=24.01h; O=23.86h). Effect of circadian phase and time since scheduled awakening was assessed by mixed effects modeling using 6 circadian and 6 time-awake bins. Results: We found no significant differences between weight groups in attentional bias for any of the food categories (p's >.05). We also saw no significant time awake effects or circadian influence on attentional bias, nor did time awake or circadian phase moderate the associations between weight category and attentional bias (p's >.05). Conclusion: Weight groups did not impact food-related attentional bias across the wake episode or circadian phase. Future directions will explore whether attentional bias for food types predicts food choice and food consumption in this study. Support: DK101046